Extended-range luminescence chronologies suggest potentially complex bone accumulation histories at the Early-to-Middle Pleistocene palaeontological site of Huéscar-1 (Guadix-Baza basin, Spain). (2nd December 2015) - Demuro, M.; Arnold, L.J.; Parés, J.M.; Sala, R.
Abstract: The palaeontological site of Huéscar-1 contains a diverse faunal assemblage and has played an important role in establishing local-scale biozone successions in the Guadix-Baza basin. Here, we provide the first ages for the fossil-bearing deposits at this site using a suite of extended-range luminescence dating approaches, including optically stimulated luminescence (OSL) of quartz 'supergrains', multi-grain and single-grain thermally transferred OSL of quartz and post-infrared infrared stimulated luminescence of K-feldspars. Assessments of luminescence characteristics and laboratory quality assurance tests indicate that the Huéscar-1 sediments are well-suited for extended-range dating applications, and the resultant chronologies obtained using different luminescence approaches display a high degree of consistency. Our combined luminescence ages reveal that the fossil-bearing fluvial sediments at this marginal lacustrine site were deposited ∼420–460 ka or possibly ∼420–570 ka, which is younger than some of the tentative late Early to early Middle Pleistocene ages inferred from faunal associations. Comparison of the dating results with taphonomic, taxonomic and geomorphic evidence suggests that the site may preserve an admixture of bones in primary depositional context and reworked fossils sourced from potentially older deposits in the surrounding valley. As such, the luminescence ages obtained for the host sediments may not be contemporaneous with all of the faunal remains preserved at Huéscar-1.